Glioma Intracraneanos - Landa Cannon, Rodolfo (1963)
We present the analysis of some clinical, pathological, radiological, electroencephalographic, and response to treatment in 100 cases of intracranial gliomas. Separately discuss each of the above mentioned aspects and will seek, where necessary to aggregate results of our findings. The material for this analysis we have 'taken from the tumors studied in the Department of Neurosurgery, National Institute of Neoplastic Diseases; some cases come from the casuistry of the Anglo American Clinic.